Effect of Integrated Postharvest Handling Practices on Quality and Shelf Life of Cactus Pear [Opuntia ficus-indica (L.) Mill.] Fruits - Shumye, Getachew; Woldetsadik, Kebede; Fitiwi, Ibrahim (Journal of Postharvest Technology, 2014)
This experiment was conducted to determine the effect of  postharvest handling practices on quality and shelf life of cactus  pear [Opuntia ficus-indica (L.) Mill.] fruits through integrating  postharvest chemical, packaging, and storage treatments. Storage  in evaporative cooler (EC) significantly improved all the quality  parameters of fruits due to the decrease in mean temperature by  2.81oC and increase of relative humidity by 11% than ambient  storage. Packaging maintained fruit quality better than that of  non-packaged ones. Similarly, chemical treatments, especially  CaCl2 and 2, 4- Dichlorophenoxyacetic acid enabled better  retention of physical and chemical quality characteristics of fruits.  The combined effects of the treatments resulted in maintenance of  lower levels of pH and higher levels of total soluble solids,  titratable acidity, ascorbic acid, pulp firmness, as well as  marketability of cactus pear fruits. Hence, the shelf life of cactus  pear fruits could be extended for two to three weeks with  nutritional quality attributes maintained in good condition using  combinations of chemicals, packaging fruits in polyethylene sheet  and then storing them under EC.
Keywords: Cactus pear; Chemical treatment Evaporative cooler; Packaging; Quality